Nyquist and Bode stability criteria to assess changes in dynamic knee stability in healthy and anterior cruciate ligament reconstructed individuals during walking. Issue 9 (14th June 2016) - Morgan, Kristin D.; Zheng, Yanbing; Bush, Heather; Noehren, Brian
Abstract: Anterior cruciate ligament (ACL) injuries are one of the most frequently injured knee ligaments. Despite reconstruction, many individuals report difficulty returning to high level activities that require greater dynamic stability. Since few methods have been tested to assess dynamic stability post ACL reconstruction (ACLR), the purpose of this study was to evaluate between and within dynamic knee stability in control and ACLR individuals using Nyquist and Bode stability criteria. Sixteen control and sixteen post ACLR individuals performed a walking protocol. Nyquist and Bode stability criteria were implemented to classify and quantify individual step-to-step sagittal plane dynamic knee stability from the gait waveforms at initial contact, 15% and 30% of stance based on the resulting gain and phase margins. An ANOVA compared differences in phase margins between the control and ACLR limbs and found that the ACLR limbs were overall significantly more unstable than the non-reconstructed and control limbs ( p =0.001). The results indicated that the ACLR individuals who exhibited stable steps adopted a more compensatory strategy aimed to stabilize the knee. These methods of evaluating dynamic knee stability may help clinicians to assess dynamic knee stability progression throughout rehabilitation and help assess return-to-sport with minimal risk to the individual.